Microcystic adnexal carcinoma—diagnostic criteria and therapeutic methods: case report and review of the literature. Issue 10 (October 2018) - Mamic, M.; Manojlovic, L.; Suton, P.; Luksic, I.
Abstract: Microcystic adnexal carcinoma (MAC) is a rare, infiltrating, locally aggressive cutaneous neoplasm of combined follicular and eccrine/apocrine histogenesis, usually presenting on the upper lip or face. Differentiation from other adnexal tumours is very important because the clinical management of these tumours is radically different, and misdiagnosis may lead to incorrect treatment. A case of recurrent MAC in the upper lip, treated with multiple excisions and postoperative radiation therapy (PORT), is presented herein. There have been no signs or symptoms of recurrence since the subsequent reconstructive surgery and PORT. Based on reports in the literature it appears that although immunohistochemistry can be helpful in distinguishing between MAC and other adnexal tumours, careful histopathological examination is essential for an accurate diagnosis. Perineural and intramuscular invasion strongly suggest the diagnosis of MAC. Its predilection for the facial area often limits the width of surgical excision. In such cases, PORT may be considered.